Social Determinants, Risk Factors, and Needs: A New Paradigm for Medical Education. (March 2022) - Muller, David; Hurtado, Alicia; Cunningham, Tara; Soriano, Rainier P.; Palermo, Ann-Gel S.; Hess, Leona; Willis, Michelle Sainté; Linkowski, Lauren; Forsyth, Beverly; Parkas, Valerie
Abstract : COVID-19 and the escalation of racism and bias that has come in its wake have had a devastating impact on health professions students. In addition to academic challenges and personal health risks, aspects of students' lives that have often gone unnoticed or inadequately addressed have come to light. Financial constraints that impact access to housing and food, neighborhood safety in light of the spike in hate crimes, and the bias inherent in the continuum from premedical education to undergraduate and graduate medical education are some examples. The authors believe that to better understand students' lived experiences and determine how to best support them, the social determinants of health framework should be applied. This framework, the social determinants of education, encompasses concepts such as social risk factors and social needs in an effort to focus more intentionally on what can be done at a policy, institutional, and individual level. In response to the pandemic, the authors expanded their appreciation of students' risk factors and needs by advancing the scope and refining the definitions of 3 key determinants: from well-being to the power of individual and communal resilience, from equity to centering racial justice, and from student health to public health and infection prevention. The authors propose applying this same paradigm to the lived experiences of staff in medical education, whose needs are often neglected in favor of students and faculty, and who, in many cases, were the most negatively impacted by COVID-19 of all the constituents in an academic health center.